Successful laparoscopic assisted myomectomy of a gigantic 9.4 kg uterine parasitic myoma: a case report and review of literature - Dash, B. B.; Kapur, Anuradha; Bahadur, Anupama (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Uterine leiomyomas are the most common benign tumours of the female pelvis affecting around 25-30% women of reproductive age. A case of successful laparoscopic assisted myomectomy in a giant uterine parasitic myoma is presented. A 42-year nulliparous morbidly obese lady presented with an Ultrasound diagnosis of a large uterine mass, detected during routine health check-up. MRI revealed a giant uterine pedunculated myoma of size 35 × 28 × 18 cm arising from the fundus and a 6 × 7 cm posterior wall myoma. After counselling the patient regarding surgical and anaesthesia risk, need of hysterectomy and laparotomy, laparoscopic myomectomy was planned. Laparoscopic findings revealed an exceptionally large parasitic fundal myoma filling the whole abdominal cavity and another 7 × 6 cm subserous myoma. main technical challenge was to tackle the big feeding vessels from the omentum providing massive blood supply to the gigantic tumor. Laparoscopic myomectomy was completed successfully using harmonic ace for coagulating the giant feeding vessels from the omentum. As the size of myoma was too big to put in the morcellation bag, so specimen retrieval was done through small incision and manual morcellation. The weight of the specimen was 9.4 Kg. This case emphasizes that size does not pose a limit to removing these gigantic myomas laparoscopically when surgical expertise and good anaesthesia facility is available. This is the case of largest myoma managed laparoscopically.